UPAYA PERLINDUNGAN HUKUM TERHADAP DESA PAK-RAMAN SEBAGAI KESATUAN MASYARAKAT HUKUM ADAT DI BALI DALAM PENGUASAAN DAN PERALIHAN TANAH ADAT - Wirta Griadhi, I Ketut (VYAVAHARA DUTA, 2012)
Abstract Land in Balinese people’s view has an important status in its relation to the whole aspect of the people’s life. Based on this view, in adat community, especially in Bali, land put into the right of the community, and the land itself called tanah adat. After the agrarian regulation called Undang Undang Pokok Agraria (UUPA), year 1960, the adat land which is included into the Ulayat Right (Hak Ulayat), still recognised by the Indonesian Nation. But in the time proces one question rises likely how to protect the desa adat (or desa pakraman in Bali) in its relation to the community right on the adat land and in its transaction with the other subject. This question could be answered by identifying the agrarian regulation in Indonesian law system, and also on the judge descision. Based on agrarian regulation and also on judge descision, the existence of the adat land and the power of the community on the adat land is still powerfull as Ulayat Right (Hak Ulayat) which recognise through the article 3 and 5 of the UUPA. There are no need to change the form of the community land right based on convertion regulation, because the ulayat right is still powerfull.